PGF2α facilitates pathological retinal angiogenesis by modulating endothelial FOS‐driven ELR+ CXC chemokine expression. Issue 1 (13th December 2022) - Zhao, Yan; Lei, Yi; Ning, Huying; Zhang, Yaqiang; Chen, Guilin; Wang, Chenchen; Wan, Qiangyou; Guo, Shumin; Liu, Qian; Xie, Ruotian; Zhuo, Yujuan; Yan, Shuai; et al.
Abstract: The pathological retinal angiogenesis often causes blindness. Current anti‐angiogenic therapy for proliferative retinopathy targets the vascular endothelial growth factor (VEGF), but many patients do not radically benefit from this therapy. Herein, we report that circulating prostaglandin (PG) F2α metabolites were increased in type 2 diabetic patients with proliferative retinopathy, and the PGF2α receptor ( Ptgfr ) was upregulated in retinal endothelial cells (ECs) from a mouse model of oxygen‐induced retinopathy (OIR). Further, disruption of the PTGFR receptor in ECs attenuated OIR in mice. PGF2α promoted the proliferation and tube formation of human retinal microvascular endothelial cells (HRMECs) via the release of ELR + CXC chemokines, such as CXCL8 and CXCL2. Mechanistically, the PGF2α /PTGFR axis potentiated ELR + CXC chemokine expression in HRMECs through the Gq /CAMK2G/p38/ELK‐1/FOS pathway. Upregulated FOS‐mediated ELR + CXC chemokine expression was observed in retinal ECs from PDR patients. Moreover, treatment with PTGFR inhibitor lessened the development of OIR in mice in a CXCR2‐dependent manner. Therefore, inhibition of PTGFR may represent a new avenue for the treatment of retinal neovascularization, particularly in PDR. Synopsis: The pathological retinal angiogenesis often causes blindness. Here we showed that PGF2α/PTGFR axis promotes to oxygen‐induced retinopathy (OIR) in mice, and PTGFR receptor may represent a novel therapeutic target for pathological retinal neovascularization, particularly for proliferative diabetic retinopathy (PDR). PGF2α/PTGFR signaling is upregulated in retina tissues from OIR mice and patients with PDR. PTGFR deletion specifically in endothelial cells markedly attenuates OIR in mice. PGF2α promotes proliferation and cord formation of human retinal microvascular endothelial cells (HRMECs) via release of ELR + CXC chemokines. PGF2α/PTGFR axis potentiates ELR + CXC chemokine expression in HRMECs through the Gq/CAMK2G/p38/ELK‐1/FOS pathway. Abstract : The pathological retinal angiogenesis often causes blindness. Here we showed that PGF2α/PTGFR axis promotes to oxygen‐induced retinopathy (OIR) in mice, and PTGFR receptor may represent a novel therapeutic target for pathological retinal neovascularization, particularly for proliferative diabetic retinopathy (PDR).